Language on the Move: Bilingualism and Local Identity in South Sulawesi Truck Expressions - Said , Ikhwan M; Abbas, Asriani; Tammasse, Tammasse; Hasan , Hasan; Zuhriah, Zuhriah; Usman, Yassir Arafat Usman; Iye, Risman (REiLA : Journal of Research and Innovation in Language, 2025)
This study addresses a notable gap in linguistic landscape research by focusing on the language variations displayed on trucks in South Sulawesi, a mobile medium of public text that has received limited scholarly attention. The research data was obtained through observation and documentation of trucks in several areas in South Sulawesi. It was found that there are 21 data which consists of Indonesian, local languages, and foreign languages. The collected data then qualitatively analyzed using content analysis techniques. The data obtained from observation and interviews were processed and thematically analyzed to explore patterns of language and cultural usage on trucks in South Sulawesi. The findings reveal that language choices align closely with socio-economic environments, where Indonesian is predominantly used in urban areas, local languages are more common in rural settings, and bilingual expressions often appear in suburban zones. These inscriptions are not only functional but also serve as markers of identity, cultural pride, and modern sensibilities, especially among younger drivers influenced by global media and popular culture. This research contributes to the broader discourse on linguistic landscapes by introducing the concept of vehicular language as a dynamic site of cultural negotiation. The insights gained have implications for sociolinguistic studies, cultural identity research, and creative industries seeking to understand how language, space, and mobility interact within Indonesia’s complex linguistic ecosystem.